Investigating Social Dynamics in the Novel Gadis Kretek by Ratih Kumala: A Literary Study of Traditional Cultural Values and Modernity - Wilujeng, Dinda Ayu; Suaedi, Hasan; Susetyo, Agus Milu (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
A novel possess a high level of complexity, including their portrayal of social dynamics. The complexity of novels is evident in their narrative structures, the characterization of characters with psychological depth and diverse backgrounds, the dynamics presented within the story, and the messages conveyed by the author. Therefore, this study investigates the social dynamics reflected in the novel *Gadis Kretek* by Ratih Kumala, focusing on social change, gender equality, and family conflicts within Indonesian society in the 1930s. The novel provides an in-depth depiction of the development of the kretek industry in Indonesia, a sector that flourished rapidly after Dutch colonization, as well as the struggle of women to find space in a male-dominated business world. The character Jeng Yah, who plays a pivotal role in kretek production, symbolizes the struggles of women confronting social and cultural limitations to prove their capabilities. Using a qualitative approach that emphasizes analysis of characters, plot, and setting, this study uncovers the tension between traditional values and modernity, as well as how changes in the kretek industry reflect significant shifts in social class. The research also explores the impact of social changes on human interactions, particularly in the context of family relationships and individual struggles to preserve their values and identities. Overall, this study provides an in-depth understanding of how the novel reflects the social, economic, and cultural transformations occurring in Indonesian society, as well as its relevance to contemporary social issues that remain significant today.